1999
DOI: 10.1046/j.1365-2141.1999.01238.x
|View full text |Cite
|
Sign up to set email alerts
|

Leukaemic presentation of small cell variant anaplastic large cell lymphoma: report of four cases

Abstract: Summary.We report four cases of a rare subtype of CD30-positive anaplastic large cell lymphoma (ALCL) with a predominant small cell component (small cell variant of ALCL) presenting with a leukaemic feature. Lymph node biopsy showed malignant cells of varying size with a predominant population of small to medium-sized malignant cells associated with large anaplastic cells strongly positive for CD30 and epithelial membrane antigen (EMA). Both large and small cells were reactive with antibody ALK1, which recogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(56 citation statements)
references
References 35 publications
4
51
0
1
Order By: Relevance
“…This evidence suggests at least the staining for CD30 and p80 in the small cells in the lymph node was only weakly positive. Furthermore, negative staining of small cells in peripheral blood for CD30 in the present case was consistent with the observation reported by Bayle et al [12]. In this study, we found that p80 was not detected in small cells in peripheral blood.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This evidence suggests at least the staining for CD30 and p80 in the small cells in the lymph node was only weakly positive. Furthermore, negative staining of small cells in peripheral blood for CD30 in the present case was consistent with the observation reported by Bayle et al [12]. In this study, we found that p80 was not detected in small cells in peripheral blood.…”
Section: Discussionsupporting
confidence: 82%
“…However, lymphoma cells (independently of cell size) in peripheral blood were unexpectedly nonreactive with the same antibodies. What is intriguing is that previous reports [12,13] showed that, in contrast to the positive nuclear and cytoplasmic staining of ALK (detected by ALK1 antibody) in large cells of the lymph node, the staining in small cells was weak and restricted to the nucleus. In those studies, the same tendency was observed in the staining for CD30 of small cells of the lymph node.…”
Section: Discussionmentioning
confidence: 45%
“…228,230,236,237 There is no reason, however, to think of this as a different disease, although spread of the disease to the peripheral blood and bone marrow may be more likely in cases of this sort. 248,249 ALK-positive lymphomas usually express T-cell markers and/or cytotoxic granule proteins, CD30, and epithelial membrane antigen and c-Myc. 219,222,228,230,250 Unlike ALK-negative cases, ALKpositive ALCLs are consistently BCL2 negative.…”
Section: The (2;5)(p23;q35) Translocation and Its Variantsmentioning
confidence: 99%
“…Presentation of ALCL in a leukemic phase, either at presentation or at relapse, has rarely been reported, mostly as case reports [9,10]. Two small series of four and three pediatric patients with ALK+ ALCL with a leukemic phase were reported by Bayle et al [13] and Onciu et al [8], respectively. In the most recent series [8], a review of the literature showed only 12 total reported cases, nine of which were pediatric patients.…”
Section: Discussionmentioning
confidence: 99%